2004
DOI: 10.1203/01.pdr.0000102702.39608.82
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cerebral Interstitial Levels of Amino Acids and Phosphorylation Potential during Secondary Energy Failure in Hypoxic-Ischemic Newborn Piglets

Abstract: The aim of this study was to determine the validity of the hypothesis that excitatory amino acids are related to phosphorylation potential during primary and secondary cerebral energy failure observed in asphyxiated infants. We report here the results of experiments using newborn piglets subjected to severe transient cerebral hypoxia-ischemia followed by resuscitation. We examined cerebral energy metabolism by phosphorus nuclear magnetic resonance spectroscopy and changes in levels of amino acid neurotransmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Physiologic variables were monitored and full intensive care was provided throughout the duration of the experiment. Previously, we showed that there were no changes in the phosphorylation potential of the brains of eight piglets over a period of 27 h under the same conditions of anesthesia as were used in the present study (18). Therefore, we assumed that any secondary energy failure observed in the test animals in this study was caused by HI injury and not by long-term effects of anesthesia.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…Physiologic variables were monitored and full intensive care was provided throughout the duration of the experiment. Previously, we showed that there were no changes in the phosphorylation potential of the brains of eight piglets over a period of 27 h under the same conditions of anesthesia as were used in the present study (18). Therefore, we assumed that any secondary energy failure observed in the test animals in this study was caused by HI injury and not by long-term effects of anesthesia.…”
Section: Methodsmentioning
confidence: 52%
“…Eight newborn piglets obtained within 24 h of birth and weighing 1.70 -1.90 kg were used in this study. The animal preparation method for the HI model has been reported in detail (18). Briefly, after sedation with an intramuscular injection of sodium pentobarbital (2 mg/kg), the umbilical artery and vein of each piglet were cannulated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 In the contralateral hemisphere, glutamate transfer seemed to be increased after hypoxia, indicating that the astrocytes were able to increase their uptake of glutamate in this phase and thus counteracted excitotoxicity. However, in the ipsilateral hemisphere, no such increase occurred.…”
Section: Neuronal Transfer Of Glutamate To Astrocytesmentioning
confidence: 99%
“…Animal Preparation The protocols for animal care were in compliance with institutional guidelines (Kusaka et al, 2004). Six newborn piglets within 48 h after birth were used.…”
Section: Methodsmentioning
confidence: 99%